Inhibitory effect of oxymatrine on serum hepatitis B virus DNA in HBV transgenic mice - Lu, Lun-Gen (World J Gastroenterol, 2004)
AIM: To study the inhibitory effect of oxymatrine on serum hepatitis B virus (HBV) DNA in HBV transgenic mice. METHODS: HBV transgenic mice model was established by microinjection, and identified by HBV DNA integration and replication. Transgenic mice with replicating HBV were divided into 3 groups, and injected with normal saline (group A, n = 9), 50 mg/kg (group B, n = 8) and 100 mg/kg (group C, n = 9) oxymatrine intraperitoneally once a day for 30 d, respectively. Quantitation of serum HBV DNA in HBV transgenic mice was performed by competitive polymerase chain reaction (PCR) in combination with DNA hybridization quantitative detection technique before and after treatment. RESULTS: Compared with pre-treatment, the serum HBV DNA in group A (F = 1.04, P = 0.9612) and group B (F = 1.13, P = 0.8739) had no changes after treatment. However, in group C serum HBV DNA was significantly decreased (F = 13.97, P = 0.0012). The serum HBV DNA after treatment was lower in group C than in groups B and A (F = 8.65, P = 0.0068; F = 12.35, P = 0.0018; respectively). The serum HBV DNA after treatment was lower in group B than in group A, but there was no statistical significance (F = 1.43, P = 0.652). CONCLUSION: Oxymatrine has inhibitory effects on serum HBV DNA in HBV transgenic mice.